Hodnocení investičního záměru společnosti - Dvořák, Marcel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Předmětem této diplomové práce je zhodnocení investičního projektu společnosti za účelem sestavení investičního doporučení pro společnost. V teoretické části diplomové práce budou uvedeny postupy, které budou aplikovány při rozhodování v praktické části práce. V té budou za pomoci těchto metod hodnoceny investiční varianty a bude sestaveno nejvhodnější investiční doporučení pro společnost.

The subjekt of this diploma thesis is evaluation of the investment project of the company in order to prepare an investment recommendation fot the company. In the theoretical part of the diploma thesis, there will be presented procedures, which will be applied in decision making in the practical part of the thesis. In this case, investment options will be assessed using these methods and the most appropriate investment recommendation for the company will be drawn up.
The Evaluation of the Investment Project of the Company
Keywords: investice; investiční rozhodnutí; finanční analýza; efektivnost investice; investiční doporučení; financování; riziko; investments; investment decision; financial analysis; effectivenes of the investment; investment recommendation; financing; risk